Pengaruh Likuidasi Pendanaan dan Inovasi Produk Terhadap Kepuasan Pelanggan pada BPR Syariah Karomah di Kabupaten Bekasi - Fitriyah Puspita; Syamsul Hadi; Abdul Asyiri; Nana Suyana (Peneliti.net, 2023)
Digital developments that are increasingly modern and fast make BPRS management continue to improve innovation and service quality to customers. The purpose of this study was to determine the effect of funding liquidity and product innovation on customer satisfaction. The research method uses a quantitative approach, because this research was carried out using a survey method with a correlation technique. Respondents in this study were BPRS Karomah customers, totaling 110 people, who had been customers for at least 1 year. Selection of the sample using purposive sampling seen from the issues raised. The results of the study show that there is a strong influence of funding liquidity and product innovation on customer satisfaction. The influence of funding liquidity and product innovation variables on customer satisfaction is 61%.